Enabling Participation in Voice Research for Adolescent Children with Characteristics of Autism - MacRae E; O'Neill J (Pennsylvania State University)
The study on which this article is based concerned children’s sense of belonging at school. Their experience of inclusion within formal education was explored from a child rights perspective using the United Nations Convention on the Rights of the Child as a guide. Most research to date has focused on the inclusion of children with autism in education from the perspective of adults, not children. As children are “experts” in their own social worlds, for this study the views of children were sought directly from them regarding their everyday experience of being at school, what they believe supports their sense of belonging at school, and what aspects of their everyday schooling could be improved. Semi-structured interviews were carried out with seven children, all of whom had characteristics of autism. The focus in this article is methodological, specifically the decision framing and decision taking of the researcher about how to provide an enabling and inviting research participation experience so that children with autism feel sufficiently comfortable and encouraged to express their views. Two key considerations in the design of this study concerned: (a) participant recruitment and (b) interview process and procedures.